Conservative treatment of early endometrial cancer. Issue 6 (25th February 2013) - Bovicelli, Alessandro; D'Andrilli, Giuseppina; Giordano, Antonio; De Iaco, Pierandrea
Abstract Endometrial cancer is the most common cancer of the female genital tract in Europe and in the United States. Endometrial cancer has increased 21% in incidence since 2008, and the death rate has increased more than 100% over the past two decades. Approximately 15% of patients with endometrial cancer are pre‐menopausal. The aim of this review is to discuss the conservative management of endometrial cancer. A number of studies largely support the conservative treatment of endometrial carcinoma (EC) in women desiring future fertility. We focus on the role of progestin hormonal therapy, including the risks associated with non‐standard care, appropriate candidate selection, expected outcomes, various progestin agents and recommended follow‐up. J. Cell. Physiol. 228: 1154–1158, 2013. © 2012 Wiley Periodicals, Inc.